Strategies for Drought Management in rain deficit conditions - Tyagi, S. K.; Singh, Ravender; Verma, Rakeshwar (Indian Farming, 2015)
India being an agriculture dependent country provides food and raw material to the exponentially increasing population. It also provides employment opportunities to strengthen our socio-economic system. Good monsoon is a key indicator for the Indian agriculture as cultivable rainfed area supplies 40% of the foodgrain demand along with supply of fodder, coarse cereals, pulses and oilseeds. Deficiency of precipitation or uneven distribution of the monsoon over a large part of the area not only impacts environmental, social and economical structure of the country but also causes worry for the farmers and keeps the managers, planners and agriculturists in a precarious situation. Strategies like developing suitable cropping systems, selection of proper crop types and varieties, adoption of proper soilwater management practices and agrometeorological advisory services are suggested to combat the agricultural drought.